Accurate Distinction of Ovarian Clear Cell From Endometrioid Carcinoma Requires Integration of Phenotype, Immunohistochemical Predictions, and Genotype: Implications for Lynch Syndrome Screening. (November 2021) - Rodriguez, Monica; Kang, Eun Young; Farrington, Kyo; Cook, Linda S.; Le, Nhu D.; Karnezis, Anthony N.; Lee, Cheng-Han; Nelson, Gregg S.; Terzic, Tatjana; Lee, Sandra; Köbel, Martin
Abstract : Ovarian clear cell carcinoma (OCCC) and ovarian endometrioid carcinoma (OEC) are both associated with endometriosis but differ in histologic phenotype, biomarker profile, and survival. Our objectives were to refine immunohistochemical (IHC) panels that help distinguish the histotypes and reassess the prevalence of mismatch repair deficiency (MMRd) in immunohistochemically confirmed OCCC. We selected 8 candidate IHC markers to develop first-line and second-line panels in a training set of 344 OCCC/OEC cases. Interobserver reproducibility of histotype diagnosis was assessed in an independent testing cohort of 100 OCC/OEC initially without and subsequently with IHC. The prevalence of MMRd was evaluated using the testing cohort and an expansion set of 844 ovarian carcinomas. The 2 prototypical combinations (OCCC: Napsin A + /HNF1B diffusely + /PR − ; OEC: Napsin A − /HNF1B nondiffuse/PR + ) occurred in 75% of cases and were 100% specific. A second-line panel (ELAPOR1, AMACR, CDX2) predicted the remaining cases with 83% accuracy. Integration of IHC improved interobserver reproducibility (κ=0.778 vs. 0.882, P <0.0001). The prevalence of MMRd was highest in OEC (11.5%, 44/383), lower in OCCC (1.7%, 5/297), and high-grade serous carcinomas (0.7%, 5/699), and absent in mucinous (0/126) and low-grade serous carcinomas (0/50). All 5 MMRd OCCC were probable Lynch syndrome cases with prototypical IHC profile but ambiguous morphologic features: 3/5 with microcystic architecture and 2/5 with intratumoral stromal inflammation. Integration of first-line and second-line IHC panels increases diagnostic precision and enhances prognostication and triaging for predisposing/predictive molecular biomarker testing. Our data support universal Lynch syndrome screening in all patients with OEC when the diagnosis of other histotypes has been vigorously excluded. Abstract : Supplemental Digital Content is available in the text.